2019
DOI: 10.1242/dev.181933
|View full text |Cite
|
Sign up to set email alerts
|

The p75 neurotrophin receptor is required for the survival of neuronal progenitors and normal formation of the basal forebrain, striatum, thalamus and neocortex

Abstract: During development, the p75 neurotrophin receptor (p75 NTR) is widely expressed in the nervous system where it regulates neuronal differentiation, migration and axonal outgrowth. p75 NTR also mediates the survival and death of newly born neurons, with functional outcomes being dependent on both timing and cellular context. Here, we show that knockout of p75 NTR from embryonic day 10 (E10) in neural progenitors using a conditional Nestin-Cre p75 NTR floxed mouse causes increased apoptosis of progenitor cells. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 56 publications
1
16
0
Order By: Relevance
“…TrkC deficiency may lead to activation of the neurotrophic receptor p75 NTR . This receptor regulates many aspects in the developing brain such as cell survival, neurite outgrowth, and, paradoxically, apoptosis, the opposite function that induces cell death (Bibel et al, 1999 ; Naska et al, 2010 ; Meier et al, 2019 ). We found that p75 NTR is expressed in the early development of the opossum cerebellum.…”
Section: Discussionmentioning
confidence: 99%
“…TrkC deficiency may lead to activation of the neurotrophic receptor p75 NTR . This receptor regulates many aspects in the developing brain such as cell survival, neurite outgrowth, and, paradoxically, apoptosis, the opposite function that induces cell death (Bibel et al, 1999 ; Naska et al, 2010 ; Meier et al, 2019 ). We found that p75 NTR is expressed in the early development of the opossum cerebellum.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the use of an Emx1 cre driver would enable the removal of Nsd1 from neural progenitor cells within the dorsal telencephalon from E9.5 . Another option would be to use a nestin cre driver to delete the Nsd1 gene from all neural stem cells from E10.5 . In this way, Nsd1 function in brain development and function could be assayed in isolation from the gastrulation deficits that presumably contribute to the embryonic lethality of null mutants .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the use of an Emx1 cre driver would enable the removal of Nsd1 from neural progenitor cells within the dorsal telencephalon from E9.5 (Zhang et al, 2019). Another option would be to use a nestin cre driver to delete the Nsd1 gene from all neural stem cells from E10.5 (Meier et al, 2019). In this way, Nsd1 function in brain development and function could be assayed in isolation from the gastrulation deficits that presumably contribute to the embryonic lethality of null mutants (Rayasam et al, 2003).…”
Section: Discussionmentioning
confidence: 99%